Uncommon Salmonella osteomyelitis in a previously healthy adult: a rare case report - Sagar, Drishti (International Journal Of Community Medicine And Public Health, 2024)
Salmonella osteomyelitis (OM) is more common in individuals with hemoglobinopathies like sickle cell anemia or thalassemia. The cardinal symptoms of OM such as fever, pain, and soft tissue swelling do not point towards a specific etiological agent. Since a preceding history of gastrointestinal infections is usually absent it causes a diagnostic challenge for Salmonella OM which is often overlooked causing a delay in diagnosis. In cases of fluoroquinolone resistance, third generation cephalosporins become the drug of choice. Due to absence of standardized guidelines, management is usually on a case-to-case basis. Previous studies have been focused mostly on children. Here, we present a rare case of Salmonella typhi OM in a 25-year male without any common predisposing factors.